2015
DOI: 10.1021/acs.energyfuels.5b01314
|View full text |Cite
|
Sign up to set email alerts
|

Compression Ignition and Exhaust Gas Emissions of Fuel Molecules Which Can Be Produced from Lignocellulosic Biomass: Levulinates, Valeric Esters, and Ketones

Abstract: This paper presents the results of combustion experiments conducted in a single cylinder compression ignition engine with several fuel molecules which can be produced from lignocellulosic biomass through a variety of processing routes. The lignocellulosic fuel 2 molecules tested were ethyl levulinate, butyl levulinate, ethyl valerate, butyl valerate, pentyl valerate, 5-nonanone, 3-heptanone, dipentyl ether and three alkanes. To ensure reliable compression ignition of all of the molecules, all of the molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The majority of existing literature proposes the use of ethyl levulinate as a sustainable blendstock for use with diesel fuel, however, the combustion reactivity of ethyl levulinate may present itself as a limiting factor in this regard. Koivistos et al [7] reported that ethyl levulinate does not ignite at the typical configuration of a tested diesel engine, also noting that ethyl levulinate/n-heptane mixtures showed the longest ignition delays of a large series of fuels tested. Similarly, Murphy et al [9] corroborate this reactivity indicator when quoting a Derived Cetane Number for ethyl levulinate of "< 5", as deduced by an ignition quality tester.…”
Section: Ethyl Levulinatementioning
confidence: 99%
See 1 more Smart Citation
“…The majority of existing literature proposes the use of ethyl levulinate as a sustainable blendstock for use with diesel fuel, however, the combustion reactivity of ethyl levulinate may present itself as a limiting factor in this regard. Koivistos et al [7] reported that ethyl levulinate does not ignite at the typical configuration of a tested diesel engine, also noting that ethyl levulinate/n-heptane mixtures showed the longest ignition delays of a large series of fuels tested. Similarly, Murphy et al [9] corroborate this reactivity indicator when quoting a Derived Cetane Number for ethyl levulinate of "< 5", as deduced by an ignition quality tester.…”
Section: Ethyl Levulinatementioning
confidence: 99%
“…Ethyl propanoate 2-butanone levulinate mixtures with a road diesel. Koivistos et al [7], in a direct injection compression ignition engine, studied a series of oxygenated fuel components both as neat fuels, and as 30 vol% blends with n-heptane. They noted a reduction in overall particulate mass when using ethyl levulinate as a fuel component, but also noted an increase in the overall number of particulate particles.…”
Section: Ethyl Levulinatementioning
confidence: 99%
“…Results show that ketone blends have proper fuel properties to use in the diesel engine without use of any additives or lubricant. This blend had slightly longer ignition delay than diesel because of carbonyl groups which make H-abstraction more difficult from ketone compared to diesel (Alkanes) [20]. NO x emissions from combustion of this fuel is slightly lower that diesel fuel which make this fuel more interesting for further investigation.…”
Section: Resultsmentioning
confidence: 98%
“…The low temperature properties of the biodiesel (cottonseed oil methyl esters and poultry fat methyl esters) were improved with the addition of ethyl levulinate. Koivistoet al conducted a study for ignition engine and observed a reduction on overall particulate mass when ethyl levulinate is used as a fuel component. Ghosh et al studied gas phase combustion kinetics of ethyl levulinate and concluded that it is more suitable as a gasoline component than a diesel fuel.…”
Section: Introductionmentioning
confidence: 99%